2005
DOI: 10.1074/jbc.m505062200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Intraflagellar Transport Complex B Core

Abstract: Required for the assembly and maintenance of eukaryotic cilia and flagella, intraflagellar transport (IFT) consists of the bidirectional movement of large protein particles between the base and the distal tip of the organelle. Anterograde movement of particles away from the cell body is mediated by kinesin-2, whereas retrograde movement away from the flagellar tip is powered by cytoplasmic dynein 1b/2. IFT particles contain multiple copies of two distinct protein complexes, A and B, which contain at least 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
114
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(118 citation statements)
references
References 52 publications
4
114
0
Order By: Relevance
“…LC‐MS/MS analysis of eluates demonstrated that IFT172 but not other IFT subunits are significantly enriched vs. the negative control suggesting that IFT57 1–234 ‐GST specifically captures IFT172 via a salt‐dependent interaction (Appendix Fig S4). The finding that IFT172 is only loosely attached to the IFT complex is in agreement with previously published results from sucrose gradient centrifugations of natively purified Chlamydomonas IFT‐B complexes (Lucker et al , 2005). On the other hand, our observation that IFT88/52 remains associated with an IFT‐B2 complex consisting of IFT80/57/54/38/20 at even 1 M NaCl is somewhat surprising as the “peripheral” IFT‐B2 subunits were previously reported to dissociate at 300 mM NaCl concentration from the IFT‐B1 complex (Lucker et al , 2005).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…LC‐MS/MS analysis of eluates demonstrated that IFT172 but not other IFT subunits are significantly enriched vs. the negative control suggesting that IFT57 1–234 ‐GST specifically captures IFT172 via a salt‐dependent interaction (Appendix Fig S4). The finding that IFT172 is only loosely attached to the IFT complex is in agreement with previously published results from sucrose gradient centrifugations of natively purified Chlamydomonas IFT‐B complexes (Lucker et al , 2005). On the other hand, our observation that IFT88/52 remains associated with an IFT‐B2 complex consisting of IFT80/57/54/38/20 at even 1 M NaCl is somewhat surprising as the “peripheral” IFT‐B2 subunits were previously reported to dissociate at 300 mM NaCl concentration from the IFT‐B1 complex (Lucker et al , 2005).…”
Section: Resultssupporting
confidence: 92%
“…IFT172 and IFT80 are both predicted to contain two N‐terminal WD40 β‐propeller domains followed by α‐solenoid structure akin to the domain architecture observed for coatomer subunits (van Dam et al , 2013). Mutations in IFT172 and IFT80 were reported to result in skeletal pattering defects (Beales et al , 2007; Halbritter et al , 2013), and the two components interact genetically (Halbritter et al , 2013) albeit not physically in sucrose gradients (Lucker et al , 2005). We observed no direct interaction between IFT172 and IFT80 in SEC (Appendix Fig S2A and B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations